Epidemiological and Clinical Features of Streptococcus dysgalactiae ssp. equisimilis stG62647 and Other emm Types in Germany - Andreas Itzek; Victoria Weißbach; David Meintrup; Beate Rieß; Mark van der Linden; Stefan Borgmann (Pathogens, 2023)
(1) Background: Streptococcus dysgalactiae subspecies equisimilis (SDSE) is an important β-hemolytic pathogen historically described as mainly affecting animals. Studies epidemiologically assessing the pathogenicity in the human population in Germany are rare. (2) Methods: the present study combines national surveillance data from 2010 to 2022 with a single-center clinical study conducted from 2016 to 2022, focusing on emm type, Lancefield antigen, antimicrobial resistance, patient characteristics, disease severity, and clinical infection markers. (3) Results: The nationwide reported invasive SDSE infections suggest an increasing infection burden for the German population. One particular emm type, stG62647, increased over the study period, being the dominant type in both study cohorts, suggesting a mutation-driven outbreak of a virulent clone. The patient data show that men were more affected than women, although in the single-center cohort, this trend was reversed for patients with stG62647 SDSE. Men affected by stG62647 developed predominantly fascial infections, whereas women suffering from superficial and fascial non-stG62647 SDSE infections were significantly younger than other patients. Increasing age was a general risk factor for invasive SDSE infections. (4) Conclusions: further studies are needed to further elucidate the raised questions regarding outbreak origin, underlying molecular mechanisms as well as sex-dependent pathogen adaptation.